Hubungan Antara Karakteristik Perawat dengan Motivasi Perawat Pelaksana dalam Menerapkan Komunikasi Terapeutik Pada Fase Kerja Di Rumah Sakit Islam Sultan Agung Semarang - Roatib, Ali; Suhartini, Suhartini; Supriyadi, Supriyadi (Department of Nursing, Faculty of Medicine, Diponegoro University, 2007)
The nursing service in a hospital is a major part of the health service given to the clients. Thus, the quality of the health service is extremely determined by the quality of the nursing service and it’s influenced by the nurse effectively in giving the nursing treatment to the clients. The importance of the nurse in guiding the trust relationship to the clients through a therapeutic communication is useful as a support in establishing the nursing treatment, in order that it can be recognized what is being required by the clients.The research want to know the relationship between the characteristic and the motivation of the performer nurse in applying therapeutic communication of working phase, by considering the nurse characteristic of the age side, sex, education, the long-term work and training. This research used correlative descriptive design using cross sectional. This research took samples of the performer nurse in Islamic Hospital Sultan Agung Semarang to 47 people using a technique of simple random sampling. The data were collected by utilizing questioner filled by the respondents.The result of univariat analysis indicates that the nurse motivation in Islamic Hospital Sultan Agung Semarang is in a high category (80,9%). While, bivariate analysis is recognized that the nurse characteristic has a significant correlation with the nurse motivation in applying therapeutic communication of working phase, that is, to the education dimension with significance 0,000, to the training dimension with significance 0,000, to the age dimension with significance 0,021, to the long-term work dimension with significance 0,034, however, there is a variable statistically not having a meaning relationship namely to the sex dimension with significance 0,135.